A transcriptional analysis of cattle immune cells reveals a central role of type 1 interferon in the In vitro innate immune response against Mycobacterium bovis - Blanco, Federico Carlos; Bigi, María Mercedes; Garcia, Elizabeth Andrea; Elola, María Teresa; Vazquez, Cristina Lourdes; Bigi, Fabiana (MDPI, 2023)
Bovine tuberculosis is a chronic infectious disease primarily caused by Mycobacterium bovis, a bacterium that affects cattle and other mammals, including humans. Despite the availability of vast research about the immune response mechanisms of human tuberculosis caused by Mycobacterium tuberculosis, the knowledge of bovine tuberculosis’s immunology, particularly regarding the innate immune response, still remains scarce. In this study, we compared the transcriptome of cell cultures containing lymphocytes and M. bovis infected-macrophages with two strains of variable virulence, the virulent Mb04-303 strain and the attenuated Mb534. To that end, we infected bovine macrophages at a multiplicity of infection of one, and co-cultured the infections with autologous lymphocytes. RNA obtained from the co-cultures was sequenced to identify differentially expressed gene pathways by using the database Reactome. The RNA-seq analysis showed that the Mb04-303 infection upregulated the type 1 interferon signalling pathway, while it downregulated the KEAP1-NFE2L2 pathway. According to the literature, this last pathway is involved in the activation of antioxidant genes and inflammasome. In addition, the macrophages infected with Mb04-303 recruited more Galectin 8 than those infected with Mb534. This result indicates that Mb04-303 induced higher phagosome membrane damage, with the possible concomitant release of bacterial compounds into the cytoplasm that activates the type I signalling pathway. Altogether, Mb04-303 repressed the antioxidant and anti-inflammatory responses, likely impairing interleukin-1β activation, and trigged the canonical type 1 interferon signalling. Although these responses led to the control of bacterial replication during early infection, the virulent strain eventually managed to establish a successful infection.